2020
DOI: 10.3390/ijms21124199
|View full text |Cite
|
Sign up to set email alerts
|

CCR5-Mediated Signaling is Involved in Invasion of Glioblastoma Cells in Its Microenvironment

Abstract: The chemokine CCL5/RANTES is a versatile inflammatory mediator, which interacts with the receptor CCR5, promoting cancer cell interactions within the tumor microenvironment. Glioblastoma is a highly invasive tumor, in which CCL5 expression correlates with shorter patient survival. Using immunohistochemistry, we identified CCL5 and CCR5 in a series of glioblastoma samples and cells, including glioblastoma stem cells. CCL5 and CCR5 gene expression were significantly higher in a cohort of 38 glioblastoma samples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 70 publications
(137 reference statements)
0
51
1
Order By: Relevance
“…It is likely that CCR5 plays a broader role in governing cancer metastasis as maraviroc and vicriviroc reduced prostate cancer cell metastasis to the bones, brain, and viscera in immune-competent mice [22] and reduced metastasis or cellular migration in glioblastoma [54] and a variety of other malignancies [18]. Prior studies had shown that CCR5 induces cancer cell homing to metastatic sites [12,55], augments the pro-inflammatory prometastatic immune phenotype [46], and enhances DNA repair [13], providing aberrant cell survival and resistance to DNA-damaging agents.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that CCR5 plays a broader role in governing cancer metastasis as maraviroc and vicriviroc reduced prostate cancer cell metastasis to the bones, brain, and viscera in immune-competent mice [22] and reduced metastasis or cellular migration in glioblastoma [54] and a variety of other malignancies [18]. Prior studies had shown that CCR5 induces cancer cell homing to metastatic sites [12,55], augments the pro-inflammatory prometastatic immune phenotype [46], and enhances DNA repair [13], providing aberrant cell survival and resistance to DNA-damaging agents.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the expression patterns’ differences, glioblastomas are divided into three subtypes as follows: classical, proneural, and mesenchymal [ 2 ]. Because glioblastoma multiforme (GBM), a grade IV glioma [ 3 ], is one of the most aggressive primary brain tumors, recent studies and reviews have focused on deepening our understanding of the disease [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…CCL5 can act as a prognostic measure of glioblastoma patient survival, as CCL5 overexpression is associated with shorter overall survival [ 86 ]. Within the glioblastoma TME, CCL5 produced by GAMs, mesenchymal stem cells (MSCs) and tumour cells signals through CCR1, CCR5 and CD44 [ 86 , 87 , 88 , 89 ]. Similar to its ligand, CCR5 expression in glioblastoma has also been associated with poor survival [ 90 ], and this expression can be upregulated on tumour cells under hypoxic conditions as an adaptive mechanism for the adverse environment [ 91 ].…”
Section: Cytokines and Chemokines That Regulate The Immune Microenmentioning
confidence: 99%
“…With the expression of both CCL5 and its receptor CCR5, tumour cells can use the autocrine signalling circuit to regulate their own proliferation, through activation of the phosphoinositide 3-kinase (PI3K)/AKT pathway. Targeting this signalling pathway with pharmacological inhibitors such as CCR5 blocker Maraviroc, PI3K/AKT inhibitor LY294002 and PI3K inhibitor NVP-BKM120 can suppress tumour cell proliferation [ 87 , 90 , 92 , 93 ]. The link between the CCL5/CCR5 pathway and tumour growth is also evident in vivo, as knockdown of CCR5 in tumour cells can significantly reduce tumour size and expression of the proliferation marker Ki67 [ 90 ].…”
Section: Cytokines and Chemokines That Regulate The Immune Microenmentioning
confidence: 99%